Proton magnetic resonance spectroscopy of neurometabolites in the hippocampi of aggressive and tame male rats - R. G. Gulevich; A. E. Akulov; S. G. Shikhevich; R. V. Kozhemyakina; I. Z. Plyusnina (Вавиловский журнал генетики и селекции)
Proportions of major neurometabolites with regard to their total amount in the dorsal region of the hippocampus were studied in adult male rats of populations selected for long for increase and absence of aggressivefearful response to humans and in unselected vivarium- kept rats by 1H magnetic resonance spectrometry. Tame and unselected males showed no significant differences in the proportions of any neurometabolites studied. Differences in the proportions of some neurometabolites were found in aggressive vs. tame and in aggressive vs. unselected animals. Tame animals showed higher proportions of GABA, N-acetylaspartate (NAA), and choline derivatives and a lower proportion of phosphorylethanolamine than aggressive ones. It is likely that the elevated content of GABA, one of the main inhibitory neurotransmitters in the brain, lowers excitation intensity in tame pups in comparison to aggressive ones. In comparison to unselected animals, aggressive rats demonstrated higher proportions of glutamine, aspartate, phosphorylethanolamine, and lactate and lower proportions of NAA and creatinine+ phosphocreatinine. Aspartate is one of the main excitement transmitter, and its elevated proportion in the brain of aggressive rats may favor more intense excitation than in unselected rats. In contrast, the elevated proportion of glutamine in aggressive rats vs. tame rats may be indicative of (1) a metabolic disturbance in the glutamate–glutamine cycle, which links neural and glial cells, and (2) decrease in the activity of glutaminase, the enzyme converting glutamine to glutamate (GABA precursor). The reduced NAA proportion together with the elevated proportion of glutamine in aggressive rats point to impaired energy metabolism in comparison to unselected animals. The differences in neurometabolite patterns between hippocampi of male rats of the unselected and aggressive populations suggest the existence of different neurobiological mechanisms governing aggression manifestation.